Using web components a new direction for modern web development - Davis, Scott 1971- (O'Reilly Media, 2016)
"We've been talking about "web pages" since we first started talking about the Web. However, with core changes to the web coming fast, it's time for every JavaScript developer to start thinking smaller. Much smaller. Instead of focusing on pages, web frameworks like Angular are doubling down on the use of Web Components to build reusable page elements. This video introduces you to the four core aspects of Web Components: Custom Elements, HTML Imports, Templates, and Shadow DOM. Understanding this technology will make it easier for any JS developer working in any framework - not just Angular, but Ember, React and more - to transition to the next generation of those frameworks. With every major browser advancing quickly toward implementation of native support for Web Components, the time to learn is now."--Resource description page.
Title from resource description page (viewed March 31, 2016)
Keywords: User interfaces (Computer systems) -- Design; User-centered system design; Human-computer interaction; Web applications; Programming languages (Electronic computers); JavaScript (Computer program language); Conception participative (Conception de systèmes); Applications Web; JavaScript (Langage de programmation); User interfaces (Computer systems); Design